Development and Evaluation of New Real-Time RT-PCR Assays for Identifying the Influenza A Virus Cluster IV H3N2 Variant - Saito, Shinji; Nakauchi, Mina; Takayama, Ikuyo; Nagata, Shiho; Odagiri, Takato; Kageyama, Tsutomu (Japanese Journal of Infectious Diseases, 2019)
From 2005 to July 6, 2018, a total of 435 swine-origin influenza A H3N2 variant virus (H3N2v) infections in humans were reported in the USA. The largest H3N2v outbreak in the USA occurred in 2011–2012. This virus obtained the HA gene from the human seasonal H3N2 influenza A viruses (seasonal H3N2) via human-to-swine transmission in the mid-1990s and was classified as Cluster IV H3N2v. For early detection of public health threats associated with Cluster IV H3N2v distinct from seasonal H3N2, we developed highly specific and sensitive one-step real-time RT-PCR assays directly targeting the HA genes of Cluster IV H3N2v and seasonal H3N2. These assays are useful for the systematic surveillance and identification of Cluster IV H3N2v.